2020
DOI: 10.1186/s13075-020-02334-5
|View full text |Cite
|
Sign up to set email alerts
|

Articular involvement, steroid treatment and fibromyalgia are the main determinants of patient-physician discordance in systemic lupus erythematosus

Abstract: Background Remission or the lowest possible disease activity is the main target in the management of systemic lupus erythematosus (SLE). Anyway, conflicting data are present in the literature regarding the correlation between physician-driven definitions and patient perception of the disease. The objective of this study is to evaluate the relationship between the definition of lupus low disease activity state (LLDAS) and patient’s health-related quality of life (HRQoL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…Discordance between patients’ and physicians’ assessment of disease activity has previously been identified. 23 The good correlations between patients’ and physicians’ evaluations in the ‘low-active disease group’ support the possibility that telephone or digital consultations accompanied by Q-SLAQ and laboratory tests can replace some physical visits in selected patients. Though Q-SLAQ has several advantages over the SLAQ, especially in daily clinical practice, the original SLAQ may be more useful in epidemiological or multinational studies, particularly since the SLAQ is translated and validated to many languages.…”
Section: Discussionmentioning
confidence: 97%
“…Discordance between patients’ and physicians’ assessment of disease activity has previously been identified. 23 The good correlations between patients’ and physicians’ evaluations in the ‘low-active disease group’ support the possibility that telephone or digital consultations accompanied by Q-SLAQ and laboratory tests can replace some physical visits in selected patients. Though Q-SLAQ has several advantages over the SLAQ, especially in daily clinical practice, the original SLAQ may be more useful in epidemiological or multinational studies, particularly since the SLAQ is translated and validated to many languages.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of active disease manifestations, we found that skin lesions were significantly linked to depression in our cohort. It is well-known from the literature that patients’ main concerns are often related to mild manifestations, such as musculoskeletal and mucocutaneous ones, due to their greater impact on patients’ degree of functioning and body image, rather than to major organ involvement and this may determine a discordance between patient and physician assessment of SLE disease status ( 17 , 18 ). Similarly to the results of this study, Eldeiry et al recently observed a prevalence of anxiety and depression of 34% and 27%, respectively, in a cohort of 341 SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study (71), past and ongoing joint involvement, a concomitant diagnosis of fibromyalgia and ongoing glucocorticoid treatment may represent the most important variables determining the poor concordance between patient and physician perspective on the disease. Actually, chronic pain represents a pervasive symptom in SLE patients.…”
Section: Treat-to-target and Patient-reported Outcomesmentioning
confidence: 99%
“…• Clinical remission is attainable in real life, for patients who are unable to reach clinical remission, LLDAS is an alternative target of treatment, being able to reduce severe damage accrual (59-65); • The LupusPRO survey tool was more sensitive than generic SF-36 scare in recognising changes of disease activity and organ damage (67); • Anxiety, depression, chronic pain and fatigue have a negative impact on patients' quality of life and should therefore be assessed and properly treated; patients should be educated and encouraged to self-empowerment (67)(68)(69)(70)(71)(72)(73).…”
Section: Take Home Messagesmentioning
confidence: 99%